Thermo – mechanical properties of SPS produced self-healing thermal barrier coatings containing pure and alloyed MoSi2 particles. Issue 12 (September 2018) - Kulczyk-Malecka, Justyna; Zhang, Xun; Carr, James; Nozahic, Franck; Estournès, Claude; Monceau, Daniel; Carabat, Alexandra L.; Sloof, Willem G.; van der Zwaag, Sybrand; Withers, Philip J.; Xiao, Ping
Abstract: Yttria – partially stabilised zirconia (YPSZ) MoSi2 composites have been designed to prolong the lifetime of the matrix by self – healing cracks during thermal cycling. The healing reaction at high temperatures is based on the decomposition of MoSi2, leading to a volumetrically expanding reaction product, which seals the crack. In this work, coefficient of thermal expansion (CTE) and the fracture toughness of composites containing MoSi2 particles, produced by spark plasma sintering (SPS) have been compared to conventional YPSZ. The CTE mismatch between YPSZ and MoSi2 was found to be small, implying that thermally induced mismatch stresses will be small and the composites have a similar CTE to conventional YPSZ. Fracture toughness was found not to be affected by the particles and showed similar values to unreinforced YPSZ. Cracks introduced by indentation have been shown neither to prefer, or avoid, the particles suggesting that such a composite system is capable of autonomously activating the self – healing reaction.